Unjuk Kerja Kotak Pendingin Peltier dengan Unit Pembuang Panas Heat Sink Fin-Fan dan Single Fan Heat Pipe - Mirmanto, M.; Alit, Ida Bagus; Anggani, Yudi (Rekayasa Mesin, 2019)
Nowadays, technology is growing rapidly. A refrigerator is one of the technology applications by using heat transfer phenomena. However, the existing refrigerators in big size, need large power, and able to damage the ozone because most of the refrigerators utilize CFC. It is necessary to create a compact refrigerator with low energy needed and environmental friendly. In this study, a small cooler box of 24.5 cm x 20 cm x 28.5 cm with 2 modules Peltier SP 1848-27145 type arranged in cascade was used as a refrigerator. The data were logged by using the data logger DAQ MX 9714 NI that was connected to the PC by using LabView. In this experiment, 22 Watt of the electric power was used and 350 ml water was placed on the cooler box room. The results show that the temperature of the cooler box room with a single fan heat pipe is lower than the heat sink fin-fan. Furthermore, the temperature of the cooler box room with the single fan heat pipe where 350ml water was placed is lower than the cooler box room without the single fan. Moreover, the COP of the cooler box is significantly affected by the heat dissipation unit.